Chemical Compositional Analysis of Catalytic Hydroconversion Products of Heishan Coal Liquefaction Residue - Xiaoming Yue; Yajun Wu; Shuangquan Zhang; Xiaoqin Yang; Xianyong Wei (International Journal of Analytical Chemistry)
Liquefaction residue of Heishan bituminous coal (HLR) was subject to two hydroconversion reactions under 5 MPa initial pressure of hydrogen at 300°C for 3 h, without catalyst and with acid supported catalyst (ASC), respectively. The reaction products were analyzed with gas chromatography/mass spectrometer (GC/MS). The results show that 222 organic compounds were detected totally in the products and they can be divided into alkanes, aromatic hydrocarbons (AHCs), phenols, ketones, ethers, and other species (OSs). The yield of hydroconversion over the ASC is much higher than that without catalyst. The most abundant products are aromatic hydrocarbons in the reaction products from both catalytic and noncatalytic reactions of HLR. The yield of aromatic hydrocarbons in the reaction product from hydroconversion with the ACS is considerably higher than that from hydroconversion without a catalyst.